Penilaian Penentuan Karyawan Terbaik Menggunakan Metode Simple Additive Weighting - Kemala Sari Siregar, Guna Yanti; Wulandari, Ika Arthalia (Jurnal Komtika (Komputasi dan Informatika), 2020)
Competition in service quality between companies requires companies to make improvements and improve the quality of Human Resources continuously. BPR Inti Dana Sentosa always strives to improve internal quality on a regular and ongoing basis by evaluating the human resources involved in the production process. HR assessment is still done by a manual method so that the process becomes very slow, and the results obtained are not accurate, even it seems subjective. While objectivity is needed to support the right decision to employ useful human resources for an extended period. This study aims to assist BPR Inti Dana Sentosa in deciding on employee assessment results by implementing the Simple Additive Weighting method. Based on nine processed employee sample data, it founded that the employee with the code 'Employee 2' was the best employee candidate. This result proves that the SAW method can help the decision-making process in the problem of determining the best employee of a company.